Interrupted breast-feeding: the experience of women-mothers - Lima, Ana Paula; Javorski, Marly (Revista de Enfermagem UFPE on line, 2009)
ABSTRACT Objective: to analyze the perception of women who had precociously weaned the children on the experience of the breastfeeding. Methodology: this is about a research from qualitative approach, performed in a Baby Friendly Hospital, in Recife city, Pernambuco, and had as participants nine mothers who were with their six-months-old babies. Data had been collected through half-structuralized interview and after, we analyzed them according to the techniques of thematic analysis. This study has been approved by the Research Ethics Committee of the Agamenon Magalhães Hospital in Recife city (protocol number 149/05). Results: the analysis of subjects disclosed that women, although knowing and repeating the speech technician concerning to breastfeeding, do not suckle the children until the sixth month of life. All, at first, told causes that let them free of the decision to wean. The analysis also emphasized women re-interpret the meanings of breastfeeding through the influence of third, this influence may be positive or negative in the course of lactation. Breast-feeding showed for these women as an experience that awakes ambivalent feelings, pleasant and at times and stressfull at others. Conclusion: while being a health professional, we need to relearn to hear the mothers and to promote the breastfeeding on the basis of reality of each woman, understanding that the practical of suckling the baby is also determined by the representations of the society where she is inserted. Descriptors: breastfeeding; weaning; maternal and child health. RESUMO Objetivos: analisar a percepção de mulheres, que desmamaram os filhos precocemente sobre a vivência da amamentação. Metodologia: pesquisa com abordagem qualitativa, realizada em um Hospital Amigo da Criança, em Recife, Pernambuco, tendo como sujeitos nove mães de bebês na faixa etária de zero até seis meses. Os dados foram coletados pela técnica de entrevista com roteiro semi-estruturado. Após a transcrição das entrevistas, estas foram analisadas segundo a técnica de análise temática. O projeto de pesquisa foi aprovado pelo Comitê de Ética em Pesquisa do Hospital Agamenon Magalhães em Recife (número de protocolo149/05). Resultados: a análise dos temas revelou que as mulheres, apesar de conhecerem o discurso técnico do aleitamento materno, não amamentam os filhos até o sexto mês de vida. Todas, a princípio, relataram causas que as isentavam da decisão de desmamar. Elas também re-interpretam os significados da amamentação por meio da influência de terceiros, podendo esta influência ser positiva ou negativa no curso da lactação. A amamentação revelou-se para estas mulheres como uma experiência que desperta sentimentos ambivalentes, ora agradável ora desconfortante. Conclusão: enquanto profissionais da saúde, precisamos re-aprender a ouvir as mulheres-mães e promover a amamentação com base na realidade de cada uma, compreendendo que a prática de aleitar o filho também é determinada pelas representações da sociedade em que está inserida. Descritores: aleitamento materno; desmame; saúde materno-infantil. RESUMEN Objetivo: analizar la opinión de las mujeres, que habían destetado los niños precociously, en la experiencia del amamantamiento. Metodología: investigación cualitativa, celebrada en um Hospital Amigo del Niño, en Recife, Pernambuco, y lo tenía como los ciudadanos nueve madres de bebés en el etária congriegan hasta seis meses. Los datos habían sido recogidos por la técnica de entrevista con guión mitad-structuralized. Después de que la transcripción de las entrevistas, éstas hubiera sido analizada según técnica del análisis temático. El estudio fue aprobado por el Comité de Ética del Hosptial Agamenon Magalhães en Recife (númerod de registro 149/05). Resultados: el análisis de los temas divulgó que las mujeres, aunque conocer al técnico del discurso del aleitamento maternal, no amamantan los niños hasta el sexto mes de la vida. Todos, el principio, habían dicho a causas ese isentavam ellos de la decisión destetar. También invierten interpretación de los significados del amamantamiento por medio de la influencia del tercera, pudiendo esta influencia positiva o negativa a estar en el curso de la lactancia. Amamantamiento demostrado para estas mujeres como experiencia que despierta sensaciones ambivalentes, sin embargo desconfortante al menos agradable. Conclusión: mientras que son profesionales salud, necesitamos aprender de nuevo a oír a las mujer-madres y promover el amamantar en base de la realidad cada uno, entendiendo que la práctica del amamantar al niño también es determinado por las representaciones de la sociedad donde se inserta. Descriptores: lactancia materna; destete; salud materno-infantil.